Gender dynamics in modern agricultural value chains - Afzal, Aneela (Arid Agriculture University, Pakistan, 2019)
Presented by Aneela Afzal (Arid Agriculture University), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.